Kaunseling Kelompok Dalam Peningkatan Personaliti* - Awang, Amir (Penerbit Universiti Sains Malaysia, 1987)
This short paper deals with several aspects, namely the definition of personality, the limitations of Individual counselling In coping the growing demands for counselling, the justification for Introducing group counselling to meet these rapidly growing demands, a brief overview of the different types of group counselling for different purposes, and finally, an by way of a few research evidence to show how and In what context group counselling has been found to be effective in promoting personality changes and development.